PENERAPAN TEORI DIFFUSION OF INNOVATION DALAM MENILAI PERUBAHAN BENTUK CONVENIENCE STORE MENJADI HYBRID CONVENIENCE STORE DI SURABAYA - Sia Lili (CALYPTRA, 2015)
This study aims to identify and analyze the influence of relative advantage, compatibility, complexity, trialiaility, observability of the respondent's interest to try toeat in a hybrid convenience store. This study uses diffusion of innovation theory basis of Roger. This study was conducted in a hybrid convenience store in Surabaya. This research using SPSS 16 software. Sampling technique used was non- probability sampling with purposive sampling and data obtained directly from the respondents. The samples used in this study was 167 respondents. The results of this study indicate that relative advantage, compatibility, trialability, observability has a significant influence on the respondent's interest to try to eat in a hybrid convenience store. However complexicity variable has no significant effect on the respondent's interest to try to eat in a hybrid convenience store.